Athena to Barbie : bodies, archetypes, and women's search for self - Wright, J. Lenore, 1972- (Fortress Press, 2021)
"Athena to Barbie explores the vexed nature of being a woman. It maps the four corners of impossible choice a female faces because of the female body--her body as spiritual space (Mary), as political space (Athena), as erotic space (Venus), and as materialist space (Barbie). The book tracks the difficulty women face in understanding themselves as someone who has, but is not only, a body. The question of identity is particularly fraught and complicated when it comes to women--because the ability to bear children is a double-edged sword. Across time (including right now), having a womb has shaped how women are viewed and treated in negative ways, and women's childbearing abilities have been used to stereotype, oppress, and constrain them. Pregnancy is powerful, but the possibility of pregnancy comes with impossible pressures and choices. This book takes on the task of reconciliation--how women can understand themselves in light of their bodies--through an intense dive into history, art, literature, theology, and, particularly, philosophy."--